Usability of Postbiotics in Ruminant Nutrition and Health - Elif Rabia Şanlı (Turkish Journal of Agriculture: Food Science and Technology)
Since the ban on the use of antibiotics to promote growth in animal production in 2006, there has been a growing interest in alternative feed additives for animal production. Postbiotics, which have been utilized for this purpose in recent years, are highly promising feed additives that substitute banned substances like antibiotics. In recent years, there have been numerous studies on the utilization of postbiotics in ruminant animal nutrition. This article includes the definition of postbiotics, their properties, methods of obtaining them, and their potential applications in ruminant animal nutrition and health.